IJCM_252A: An Assessment of Functioning of Health and Wellness Centres - Sub Health Centres (HWC-SHC) in Raipur District. - Thakur Barkha; Jain Kamlesh; Sinha Ashish; Chandrakar Aditi (Wolters Kluwer Medknow Publications, 2024)
Background: The National Health Policy 2017 has envisioned the integration of Health and Wellness Centers (HWCs) into India's healthcare system as part of Ayushman Bharat. In February 2018, the Indian Government declared the transformation of 1,50,000 existing Sub Health Centers and Primary Health Centers into Health and Wellness Centers (HWCs) to provide Comprehensive Primary Health Care (CPHC). Health and Wellness Centres have an important role in the prevention of several diseases and health promotion and in undertaking public health functions in the community to strengthen the frontline workers and community platforms. Objective: To assess the availability of Infrastructure and 12 comprehensive primary health care services in study centres (HWC-SHC) in Raipur district Methodology: This is a cross-sectional observational study conducted in the 32 Health and wellness centre-sub centres of Raipur district, Chhattisgarh. In the Raipur district, there are 4 blocks and from each block, 25% of the study centres (HWC-SHC) are selected by simple random sampling. Semi- structured assessment tool with the reference of Government of India Operational Guidelines was used which consisted of checklist regarding Physical Infrastructure, Human Resource, Medicine, Diagnostic, IT component and 12 comprehensive primary health care services. The data was collected and analysis is being done by using SPSS software. Results: Out of 32 HWC-SHCs, 6 (18.75% ) were catering the services for the population as per the norms i.e. 3000- 5000. In the present study, 19 (59.4%) boundary wall, and 21 (65.6%) of SCs had wellness space. There were 31 (96.9%) of SCs had labor room, and 14 (43.8 %) had newborn care corner (NBCC). In this study, 21.9% Grievance board and 100% of IEC were present at the studied subcentres. It was observed that 31(96.9%) SCs had water, 27 (84.4%) had electricity supply and 1 (3.1%) of SCs had power backup. Separate public utilities for males and females were available in 2(6.3%) of the study centres. Out of the study sub-centre, 28 (87.5%) residential facilities were available, out of which 24 (85%) were occupied. For diagnostic services, 53.1 % of study centres have sickle- cell rapid tests and none of the centres have VIA for Screening of cervical cancer. Conclusion: The finding of the study shows that there is a scarcity in the physical infrastructure, Human resource and lab-diagnostic services at the studied centres. The major factor contributing to the non-utilization of health services at the SCs was the lack of adequate infrastructure, and logistics available at these centres.